ARE CHILDHOOD CRUELTY TO ANIMALS INDICATES AS MENTAL DISORDER? - Risa Juliadilla; Nia Anggri Noveni (Psychosophia: Journal of Psychology, Religion, and Humanity, 2021)
Animal Cruelty regularly happened during childhood that indicates beyond cruelty to humans. Cruelty to animals distinguishes some steps: curiosity, exploration, imitates or even the aggressive act refers to animal cruelty. The ignorance toward these aggressive acts led to Conduct Disorder or even Antisocial Personality Disorder. Animal Cruelty reached an agreement as to the unethical act with intentional tortures, unintentionally suffering causes death. Cruelty is done on purpose and with intentional time. This research aims as a reference for animal cruelty in childhood by proposing some research summary in (1) Animal Cruelty framework, (2) Animal Cruelty relation among child abuse and domestic violence; (3) Developmental Psychology reference: Children aggressive acts toward animal; (4) animal cruelty and psychology disorder and (5) clinical pathway childhood cruelty to animals. The research conducts a literature review by describing a theory, discussion, and results from textbooks, articles, and journals. The researcher analyzed, compared the results taken from some literature, identifies the pros and cons, and proposing findings and discussions. In conclusion, animal cruelty defines as a crucial marker for mental health that relates to Conduct Disorder to Antisocial Personality Disorder. The role of adults is vital in minimizing children's acts for committing animal cruelty by nurturing empathy. Adults with its role particularly required during the early stages of a child's development when adults' affirmation related to behavioral aspects of morality is necessary for children. Furthermore, character education for children consider as broad topics that not only about the animals, but the most important thing is for animals when children would learn justice, and ethics to treat animals generously. Keywords: Animal Cruelty, Childhood, Conduct Disorder, Antisocial Personality Disorder